Exploring risk profiles and emergency frequency of purchasers and non-purchasers of personal emergency alarms: A prospective cohort study - De San Miguel, K.; Lewin, Gill; Burton, Elissa; Toye, Christine; Boldy, Duncan; Howat, Peter (2015)
© 2015 De San Miguel et al. Background: Personal alarms support independent living and have the potential to reduce serious consequences after a fall or during a medical emergency. While some Australian states have government funded personal alarm programs, others do not; but user-pays services are available. Although several studies have examined the profiles of alarm users, little is known about the risk profile of non-users. Specifically, whether there are "at risk" individuals who are unable, or choose not to purchase a service, who experience a home-based emergency in which an alarm could have mitigated an adverse outcome. This study aimed to describe the 'risk profile' of purchasers and non-purchasers of alarms; explore the reasons behind the decision to purchase or not to purchase and identify how often emergency assistance was needed and why. Methods: Purchasers and non-purchasers were followed for one year in this prospective cohort study. Demographic, decision-making and risk factor data were collected at an initial face-to-face interview, while information about emergencies was collected by monthly calls. Results: One hundred and fifty-seven purchasers and sixty-five non-purchasers completed the study. The risk profiles between the groups were similar in terms of gender, living arrangements, fall history and medical conditions. Purchasers (Mean = 82.6 years) were significantly older than non-purchasers (Mean = 79.3 years), (t(220) = -3.38, p = 0.000) and more functionally dependent on the IADL (z = -2.57, p = 0.010) and ADL (z = -2.45 p = 0.014) function scores. Non-purchasers (Mean = 8.04, SD = 3.57) were more socially isolated with significantly fewer family networks than purchasers (Mean = 9.46, SD = 3.25) (t(220) = -2.86, p = 0.005). Both groups experienced similarly high numbers of emergencies, 38.2 % of purchasers and 41.5 % of non-purchasers had at least one emergency where an alarm could have assisted. Main reasons for non-purchase were: cost (77 %), limited alarm range (51 %), no need (39 %) and lack of suitable contacts (30 %). Conclusion: There are older individuals who are at high risk of an emergency who are choosing, often for financial and lack of family support reasons, not to purchase a personal alarm service. Greater availability of government funded subsidy schemes would enable these individuals to access a service. Increasing the range over which alarms work could increase their appeal to a broader range of older persons living in the community. Future research should consider how strategies that improve social isolation from family and challenge clients' beliefs about their own health and independence can support increased access to personal alarm services.